Divide et Impera in the Banten Sultanate: The Political Succession of Sultan Haji and VOC's Pepper Monopoly in the 17th and 18th Centuries - Aziz, Mukhamad Rafidah; Prabaswara, Sandya Sahisnu (Universitas Islam Negeri Sunan Kalijaga, 2023)
Nusantara's spice commodities became one of the determining factors of the global spice trade in the 17th and 18th centuries. There were three types of superior spices produced by the Nusantara such as cloves, nutmeg, and pepper. In the 17th century AD, Banten Sultanate was known as a pepper producer, and its pepper trade significantly influenced the economic and political development of the region. Apart from improving the economy, this commodity was also used to establish diplomatic relations between foreign nations. However, the pepper trade also became one of the factors that caused conflict in the Banten Sultanate. The implementation of the divide et impera strategy by the VOC caused an internal conflict between Sultan Haji and Sultan Ageng Tirtayasa. The conflict occurred when Sultan Haji allied with the VOC to succeed his father, Sultan Ageng Tirtayasa. Sultan Haji made an agreement with the VOC in 1684, allowing the company to monopolize the pepper trade. This research examines this issue by looking at the overall condition of the pepper trade before and after the VOC's presence in the Banten Sultanate and the succession of Sultan Haji through the 1684 pepper trade agreement. This qualitative research uses historical research methods with a political approach. The theory used in this research is political economy theory, which includes understanding power, economic system, and public policy. The historical research method comprises heuristics, verification, interpretation, and historiography stages. The analysis using a political approach reveals the extent to which the Banten Sultanate's pepper trade policy influenced the succession of Sultan Haji and the monopolization of the pepper trade by the VOC.